2010
DOI: 10.1007/978-3-642-12073-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Approaches to Carbon–Sulfur Bond Formation

Abstract: The transition metal mediated synthesis of carbon-sulfur (C-S) bonds is possible with a variety of simple and tailored metal complexes. This chapter serves to illustrate developments over the last decade involving the catalytic synthesis of C-S bonds with various transition metals, focusing on cross-coupling reactions and addition to p-bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 253 publications
(204 reference statements)
2
55
0
Order By: Relevance
“…Only recently have fused pyrrole–thiophene‐containing ring systems of up to ten annelated rings been realized, through Buchwald–Hartwig amination, whereas comparable sulfuration reactions are so far unmastered. Transition metal catalyzed C−S bond‐forming reactions involving thiols or thiolates are well known . The use of hydrogen sulfide surrogates such as thiourea or potassium thioacetate is a highly desirable alternative to thiols, since handling and preparation of these malodorous and often air‐sensitive compounds is avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently have fused pyrrole–thiophene‐containing ring systems of up to ten annelated rings been realized, through Buchwald–Hartwig amination, whereas comparable sulfuration reactions are so far unmastered. Transition metal catalyzed C−S bond‐forming reactions involving thiols or thiolates are well known . The use of hydrogen sulfide surrogates such as thiourea or potassium thioacetate is a highly desirable alternative to thiols, since handling and preparation of these malodorous and often air‐sensitive compounds is avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Aryl thioethers are most commonly prepared via the coupling of an aryl halide or pseudohalide with a thiol in the presence of base. 7–10 With electron deficient aryl halides, these reactions often proceed via an uncatalyzed S N Ar pathway, 7 while Pd or Cu catalysis 8 is commonly employed to forge the C–S bond with electron rich (hetero) aryl halides (Figure 2a). …”
mentioning
confidence: 99%
“…[1,2] Mechanistically, Pummerer-type reactions are proposed to proceed by nucleophilic addition to an in situ generated thionium species to form sulfur-containing motifs (Scheme 1a). [4,5] Given our recent success in applying chiral-anion phasetransfer (CAPT) catalysis to various challenges in asymmetric catalysis (Scheme 1b), [6,7] we envisioned that this strategy may be applied to the enantioselective construction of stereogenic C À Sb onds through aP ummerer-type reaction (Scheme 1c). [3] Development of this transformation would provide an enantioselective entry to carbon stereocenters,b earing sulfur,w hich were previously deemed either challenging or inaccessible.…”
mentioning
confidence: 99%
“…[7] It should be noted that direct oxidation of sulfides to thionium species using this class of oxidant has not been reported to date. This systematic investigation (entries [4][5][6][7][8][9][10] revealed that the substituent R 2 ,o nt he 3,3'-phenyl ring, is crucial (entry 6) and that ab ulky R 3 substituent further improved the enantioselectivity (entries [8][9][10]. Application of CAPT catalysis to the oxidativeP ummerertype CÀNbond-forming reaction for the synthesis of enantioenriched N,S-acetals.…”
mentioning
confidence: 99%